Craspedorrhynchus linardii, a new species of chewing louse (Phthiraptera: Ischnocera: Philopteridae) from the Gray-headed Kite (Aves: Falconiformes: Accipitridae) - Valim, Michel P. (Zootaxa, 2006)
A new species of the genus Craspedorrhynchus Kéler, 1938 (Phthiraptera: Ischnocera: Philopteridae) is described and illustrated based on specimens from a Gray-headed Kite, Leptodon cayanensis (Latham, 1790) (Aves: Falconiformes: Accipitridae), collected in Fazenda Água Limpa, Brasília-DF, Brazil. This is the first species of chewing louse described from the Gray-headed Kite.